Development, characterization, and diffusion modelling of physically cross-linked hydrogel wound dressings from cellulosic blends and sodium hydroxide/thiourea aqueous solution - Bigornia, Dax Elbert A.; Tumolva, Terence P. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Hydrogels are three-dimensional polymeric networks with solid-like appearance and with physical or chemical cross-links existing among the chains. When used as wound dressing, hydrogels have the ability to absorb wound exudates, maintain moisture or the wound, and swell several times their dry volum e without being soluble under physiological conditions. In this study, two of three cellulosics namely, hydroxyeth yl cellulose (HEC), hydroxypropyl cellulose (IIPC), and carboxymethyl cellulose (CMC), were blended to form hydrogels with 6% by weight NaOI I and 5% by weight thiourea as cross-linking agents. Characterization tests were done on the hydrogels using f TIR to identify functional groups present and SEM to determine surface morphology. Swelling ratio in distilled water and simulated body fluid media as well as its variation with pH, temperature, and cationic valence of the swelling medium were investigated. Enthalpy of mixing was evaluated using the Gibbs Helmholtz equation. Antimicrobial property of the hydrogels were also assessed. Zero order to second order swelling kinetics and power law model were applied on swelling ratio data to obtain the best fit. Diffusion coefficient was calculated using the equation described by Peppas and Brazel and diffusion models were constructed for the hydrogels obeying Fickian diffusion. Among the eighteen hydrogels synthesized , 80%CMC/20%1-IEC blend ratio was best suited as wound dressing. This blend possessed the advantages of both CMC and HEC in addition to having the highest swelling ratio in different types of media within its blend. Furthermore, its lowest enthalpy of mixing attested that it contained the strongest polymer solvent interactions among the hydrogels
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman
Keywords: Colloids; Colloids -- Synthesis